Factors Influencing the Successes of Small and Medium Enterprises: A Case Study of SMEs in Battambang City Cambodia - Tieng, Morin; Chhoeurm, Vicheka; Soeurn, Chenda; Hour, Ry; Vam, Piseth; Yoeng, Hak; Sam, Rany (International Journal of Management and Business Intelligence, 2024)
The global business sector has experienced significant growth in the twenty-first century, driving substantial expansion in the global economy. Small and medium-sized enterprises (SMEs) account for 58% of Cambodia's GDP and employ more than 70% of the workforce. This study aimed to achieve three objectives: to understand the current state of business owners and enterprise operations in Battambang, to investigate the factors that influence the success of small and medium enterprises (SMEs) in Battambang and to examine business owners' perceptions of the factors that contribute to the success of SMEs in Battambang. To ensure robust analysis, the collected information was subjected to multiple linear regression, a statistical method widely used in the social sciences, along with percentage, frequency, and averaging methods. The comprehensive findings of this study underscore several key points. First, the majority of business owners are men who have established their companies based on personal experience. Importantly, the study reveals that only two of these four variables are indispensable for business success: demographics and management skills. Demographic factors such as age, gender, education level, business experience, and management skills in planning, organizing, leading, and controlling play crucial roles in the success of SMEs.